ETIKA KOMUNIKASI PENGGUNAAN MEDIA SOSIAL “INSTAGRAM” OLEH GENERASI Z ( Studi pada Mahasiswa Fakultas FISIP UIN Raden Fatah Palembang): STUDI PADA MAHASISWA FAKULTAS FISIP UIN RADEN FATAH PALEMBANG - Agustiana, Ira; Aprianti, Reza; Astrid, Gita (Jurnal Prodi Ilmu Komunikasi, 2024)
Communications carried out on social media do not always use standard language, or language that matches Indonesian enhanced spelling (EYD), this causes many social media users to ignore aspects of values, norms and communication ethics. The social regulation system becomes mutual respect and is known as courtesy, manners, protocol and others. The purpose of the association guidelines is none other than to safeguard the interests of each involved so that they are happy, calm, peaceful, protected without harming their interests and guaranteed that their actions are carried out in accordance with prevailing customs and do not conflict with general human rights. This study aims to determine the communication ethics of using social media Instagram on students of the Faculty of Social and Political Sciences UIN Raden Fatah Palembang. The assessment approach used in this research is a qualitative research approach that uses data collection such as observation, interviews, and documentation. Based on the results of the research that the researchers have done, the researchers conclude that; The ethics of communication for the use of social media "Instagram" for Social Sciences students at Uin Raden Fatah Palembang, namely by getting to know the rules, before using social media, users are encouraged to know the rules that apply. Understand the age limit for social media users, social media does not have content filters in it, so negative images or news often appear that children should not see. Then pay attention to uploads, social media users are also expected to be very clever in sorting out personal things to upload. Filter before sharing, because those who still swallow the information they get raw and immediately spread the news without knowing the truth, causing hoax news to go viral faster, especially when using social media.